The 12 Touchstones of Good Teaching : a Checklist for Staying Focused Every Day - Goodwin, Bryan; Hubbell, Elizabeth Ross (ASCD, 2013)
Find out how a simple, practical checklist can help you cut through the clutter of information to make more deliberate, thoughtful decisions in your everyday practice. This book presents a checklist of 12 daily touchstones that can help educators take the right actions, engage in more thoughtful behaviors, and stay focused on the hallmarks of effective instruction.